2012
DOI: 10.1186/1750-9378-7-9
|View full text |Cite
|
Sign up to set email alerts
|

Activating KIR/HLA complexes in classic Kaposi's Sarcoma

Abstract: BackgroundClassic Kaposi's Sarcoma (cKS) is a rare vascular tumor associated with Human Herpesvirus 8 (KSHV) infection, nevertheless not all KSHV-infected individuals have cKS.ObjectiveWe investigated whether particular KIR/HLA receptor/ligand genotypes would be preferentially present in KSHV-infected and uninfected individuals who have or have not developed cKS.MethodsKIR/HLA genotypes were analyzed by molecular genotyping in 50 KSHV-infected individuals who did or did not have cKS and in 33 age-and sex-match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 18 publications
4
20
2
Order By: Relevance
“…An imbalance in the ratio of NK inhibitory and activating receptors is present in a number of diseases [27], and it was clari ed that KIR/HLA interactions in uences both susceptibility and protection towards infective diseases [28][29][30][31][32]. Within the scenario of infectious diseases, an increased expression of inhibitory NK cell receptor on the CD56-CD16 + NK cells was shown to be present in HIV-infected viremic patients and to result in the inhibition of CD16-induced cytotoxicity [18].…”
Section: Discussionmentioning
confidence: 99%
“…An imbalance in the ratio of NK inhibitory and activating receptors is present in a number of diseases [27], and it was clari ed that KIR/HLA interactions in uences both susceptibility and protection towards infective diseases [28][29][30][31][32]. Within the scenario of infectious diseases, an increased expression of inhibitory NK cell receptor on the CD56-CD16 + NK cells was shown to be present in HIV-infected viremic patients and to result in the inhibition of CD16-induced cytotoxicity [18].…”
Section: Discussionmentioning
confidence: 99%
“…The first studies on associations between human leukocyte antigen (HLA) alleles and KS were performed prior to the discovery of KSHV as the causative agent [1621]. Most recently, HLA association studies of KS have mainly focused on AIDS-KS [2226], with few investigating transplant-related KS [27–30] or classic KS [3134]. Some of these studies have identified both HLA class I [22, 23, 27, 33, 35] and class II [24, 33] as associated with an increased risk for KS.…”
Section: Introductionmentioning
confidence: 99%
“…An imbalance in the ratio of NK inhibitory and activating receptors is present in a number of diseases [27], and it was clari ed that KIR/HLA interactions in uences both susceptibility and protection towards infective diseases [28][29][30][31][32]. Within the scenario of infectious diseases, an increased expression of inhibitory NK cell receptor on the CD56-CD16 + NK cells was shown to be present in HIV-infected viremic patients and to result in the inhibition of CD16-induced cytotoxicity [18].…”
Section: Discussionmentioning
confidence: 99%